Construction of an Optimum Currency Area Index Anchored to the Gold Dinar: The Case of Selected Islamic Countries - Agustiar, Memet; Djafar, Fariastuti; Afrizal, Afrizal (International Journal of Economics and Financial Issues, 2017)
This paper constructs an Optimum Currency Area (OCA) Index by using the gold price as a nominal anchor and substitute for the US Dollar. The use of gold Dinar is in line with the spirit for implementing Sunnah money (gold Dinar). The method used for estimating the OCA-gold Index is the standard deviation of gold price variability. The five Islamic countries selected as the units of observation are listed among the top ten gold consumer countries worldwide. The findings of this paper may help us to understand how powerful gold can be as a benchmark or convergence criterion for a cycle co-movement measure of symmetry shock within the Islamic nations in comparison to the US Dollar. As most of the OCA's conventional index have adopted fiat money (Dollar and Euro) as an anchor, this study offers an alternative model that employs the use of commodity money as the benchmark. Keywords: Optimum Currency Area, Gold Dinar, Islamic Nation, Anchor Currency JEL Classifications: E42, F36, F33